Percutaneous transluminal angioplasty for treatment of chronic cerebrospinal venous insufficiency in people with multiple sclerosis: a summary of a Cochrane systematic review. Issue 4 (18th June 2013) - van Zuuren, Esther J; Fedorowicz, Zbys; Pucci, Eugenio; Jagannath, Vanitha; Robak, Edward W
Abstract : Background: It has been recently hypothesised that chronic cerebrospinal venous insufficiency (CCSVI) may be an important factor in the pathogenesis of multiple sclerosis (MS). The proposed treatment for CCSVI is percutaneous transluminal angioplasty, also known as the 'liberation procedure', which is claimed to improve the blood flow in the brain, thereby alleviating some of the symptoms of MS. Our objective was to determine the effects of percutaneous transluminal angioplasty used for the treatment of CCSVI in people with MS. Methods: We searched the following databases up to June 2012 for randomised controlled trials: The Cochrane Multiple Sclerosis and Rare Diseases of the Central Nervous System Group Specialised Register, CENTRAL, in The Cochrane Library 2012, Issue 5, MEDLINE (from 1946), EMBASE (from 1974) and reference lists of articles. We also searched several online trials registries for ongoing trials. Results: Our searches retrieved 159 references, six of which were related to ongoing trials. No randomised controlled trials met our inclusion criteria. Conclusions: There is currently no high level evidence to support or refute the efficacy or safety of percutaneous transluminal angioplasty for treatment of CCSVI in people with MS. Clinical practice should be guided by evidence supported by well-designed randomised controlled trials: closure of some of the gaps in the evidence may be feasible at completion of the six ongoing clinical trials.